1999
DOI: 10.1530/jrf.0.1150215
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody that recognizes an epitope of the sperm equatorial region and specifically inhibits sperm-oolemma fusion but not binding

Abstract: Balb/c mice were immunized with purified hamster sperm heads for induction of antisera and the production of monoclonal antibodies that recognize preferentially the equatorial segment. Twenty-six hybridoma clones secreted monoclonal antibodies with strong affinity for spermatozoa. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Several research groups have previously identified immunoreagents that react with equatorial segment proteins similar in size to ESP [8,10,11]. Noor and Moore [10] purified and injected hamster sperm heads into mice and raised monoclonal antibodies with strong affinity for spermatozoa.…”
Section: Esp: a Protein Concentrated In The Equatorial Segment Of Matmentioning
confidence: 99%
See 2 more Smart Citations
“…Several research groups have previously identified immunoreagents that react with equatorial segment proteins similar in size to ESP [8,10,11]. Noor and Moore [10] purified and injected hamster sperm heads into mice and raised monoclonal antibodies with strong affinity for spermatozoa.…”
Section: Esp: a Protein Concentrated In The Equatorial Segment Of Matmentioning
confidence: 99%
“…Noor and Moore [10] purified and injected hamster sperm heads into mice and raised monoclonal antibodies with strong affinity for spermatozoa. One of their monoclonal antibodies (M1) recognized the equatorial segment of hamster sperm, as revealed by immunofluorescence microscopy, and bound protein bands of 37.5 and 34 kDa on a Western blot.…”
Section: Esp: a Protein Concentrated In The Equatorial Segment Of Matmentioning
confidence: 99%
See 1 more Smart Citation
“…Other proteins are also present in the sperm equatorial region, as shown by immunofluorescent and electron microscopy. Among them, the proteins recognized by antibodies M29 [22], M1 [23], G11, and G13 [24] appear after the acrosome reaction, whereas oscillin is revealed in permeabilized spermatozoa [25]. A set of fusion-related soluble N-ethylmalameide-sensitive factor attachment protein receptors (SNAREs) also occur in the equatorial region of a wide variety of mammalian spermatozoa [26].…”
Section: Introductionmentioning
confidence: 99%
“…Molecules located in the equatorial segment include the mouse 38 -48 kDa complex protein, equatorin, which can inhibit the sperm-egg fusion process in vitro and in vivo (Yoshinaga et al, 2001a), and M1, a hamster 37.5 and 34.0 kDa protein (Noor and Moore, 1999). G11/M13, a guinea pig 34 kDa protein changes its conformation during the acrosome reaction (Allen and Green, 1995).…”
Section: Acrosomal Modifications Duringmentioning
confidence: 99%